Meningkatkan Daya Saing UMKM Rumah Tempe Indonesia Cabang Bandung melalui Sustainable Competitive Advantage - Nurul Mardhiah Sitio; Tofa Waluyo Alifya; Gessan Kurnia Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
Rumah Tempe Indonesia (RTI) need a marketing strategy to improve their business continuity. This study analyzes the Sustainable Competitive Advantage formulated with the VRIO model in business model development to formulate a marketing strategy. The data collected by using the in-depth interviews, observations, and several external sources. The results of the analysis indicated that the RTI has a competitive advantage in two aspects, in terms of its human resources and the company ability to survive. The result of competitive ability in this research show there are two marketing strategies that can be implemented by the MSMEs, the use of its social media and collaboration with the promotional services from community leaders and local celebrities to increase the brand awareness of Rumah Tempe Indonesia branch Bandung and also for its products.